2011
DOI: 10.1017/s0007114511005290
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the extracellular matrix of lung during zinc deficiency

Abstract: Suboptimal intake of Zn is one of the most common nutritional problems worldwide. Previously, we have shown that Zn deficiency (ZD) produces oxidative and nitrosative stress in the lung of rats. We analyse the effect of moderate ZD on the expression of several intermediate filaments of the cytoskeleton, as well as the effect of restoring Zn during the refeeding period. Adult male rats were divided into three groups: Zn-adequate control (CO) group; ZD group; Zn-refeeding group. CerbB-2 and proliferating cell nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
2
10
0
1
Order By: Relevance
“…Consistent with reports associating severe Zn deficiency with oxidative stress and inflammation in other tissues [6-9,11,47], we found that marginal Zn deficiency was also associated with oxidative stress and inflammation in both the ductal epithelium and adipocyte-rich stroma in the mammary gland. An important component of the stroma is the protein collagen.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with reports associating severe Zn deficiency with oxidative stress and inflammation in other tissues [6-9,11,47], we found that marginal Zn deficiency was also associated with oxidative stress and inflammation in both the ductal epithelium and adipocyte-rich stroma in the mammary gland. An important component of the stroma is the protein collagen.…”
Section: Discussionsupporting
confidence: 92%
“…Excess collagen directly inhibits mammary gland expansion [48] and has major implications for breast disease risk [49]. Consistent with reports that Zn deficiency increases inflammation and fibrosis in lung [47], we observed enhanced collagen accumulation, primarily in the peri-ductal region, associated with Zn hyperaccumulation and oxidative stress in Zn deficient mice. This likely created a physical barrier that impeded ductal elongation in addition to altering the microenvironment of the mammary gland.…”
Section: Discussionsupporting
confidence: 89%
“…It is also notable that zinc deficiency is associated with inflammatory alterations of lung extracellular matrix predisposing to fibrosis (111). This finding is of particular interest in view of the presence of interstitial pulmonary fibrosis in cOVId-19 patients (112).…”
Section: Zinc and Lung Inflammationmentioning
confidence: 99%
“…Adequate zinc levels in the body protect against oxidative stress caused by reactive oxygen species (ROS) [ 39 ]. Zinc deficiency promotes the production of proinflammatory cytokines and is linked with the inflammatory alteration of lung predispose to fibrosis [ 40 ]. Supplementation of a moderate dose of zinc has been shown to correct the overproduction of proinflammatory cytokines in the elderly caused by zinc deficiency [ 41 ].…”
Section: Minerals and Immune Systemmentioning
confidence: 99%